Management of Urgent Bleeding in Patients with Hemophilia A: Focus on the Use of Emicizumab - Jiménez-Yuste, Víctor; Álvarez-Román, María T.; Berrueco, Rubén; Bonanad, Santiago; Calvo-Villas, José M.; González-González, Rebeca; Porras, José R. González; Núñez-Vázquez, Ramiro J.; Rodríguez-López, Manuel (TH Open, 2024)
Management of patients with hemophilia A (HA) requires the knowledge and experience of specialized health care professionals. However, these patients may need to be attended in emergencies, outside the referral hospital, where health care professionals do not know about hemophilia and/or new innovative treatments.This study aimed to develop a simple and practical algorithm that could be used in emergency situations by nonspecialized treaters in HA and bleeding with or without factor VIII (FVIII) inhibitors under emicizumab prophylaxis.A group of experts agreed on a simple algorithm, easy to operate, adapted from previous international guidelines, and based on their clinical experience.The proposed algorithm starts with identifying the patient, confirming the diagnosis of HA, prophylaxis with emicizumab, and/or use of other treatments. After stabilizing the patient and stratifying the bleeding risk, the patient is managed according to the presence/absence of FVIII inhibitors. Patients without FVIII inhibitors should receive FVIII concentrate. Dose and follow-up depend on bleeding localization and severity. Patients with FVIII inhibitors should preferably receive recombinant activated factor VII as bypass agent. A basic coagulation assay, FVIII assessment, and FVIII inhibitors detection assays are necessary in an emergency. However, these tests should be interpreted with caution and appropriately chosen, as emicizumab may alter the results.The management of patients with HA is challenging in emergency situations, especially if they are treated with new agents. Nonspecialized in coagulopathies health care professionals have limited understanding of the disease, highlighting the need for an algorithm to assist them in making informed decisions.
Keywords: hemophilia; emicizumab; emergency; bleeding; inhibitors